State-of-the-art signal amplification strategies for nucleic acid and non-nucleic acid biosensors - Ijaz Gul; Muhammad Akmal Raheem; Md. Reyad-ul-Ferdous; Xi Yuan; Zhenglin Chen; Chenying lv; Minjiang Chen; Jiansong Ji; Duanpo Wu; Qiang Zhao; Chenggang Yan; Dongmei Yu (Sensors and Actuators Reports)
Biosensors have garnered substantial attention as an emerging toolbox for analyzing biomarkers, physiological processes, food, and environmental metrices. Rapid, sensitive, and selective detection is pivotal to the practical utility of a biosensing system. Over the last few years, strides have been made in biosensing research to develop next-generation sensing systems that meet WHO's ASSURED criteria. Shorter response times, accuracy, high sensitivity, and selectivity are immensely important parameters of a biosensor, directly impacted by the biosensing signal generation and detection modality. Herein, we critically analyze the state-of-the-art signal amplification strategies for various nucleic acid and non-nucleic acid bioanalytes to improve the analytical performance of biosensing systems. We first provide a brief overview of the key components of biosensors. Next, we provide insights on state-of-the-art signal amplification strategies by dividing them into target preamplification, target enrichment, cascade reactions, biocomponent engineering, exploring functional materials, optimizing reaction conditions, designing novel microfluidic devices, and harnessing AI, along with selected examples. We evaluate the development trends of these signal enhancement approaches and discuss pros and cons of each approach. Finally, we highlight current challenges and future considerations for this emerging interdisciplinary research area.